Penguatan Kesadaran Masyarakat atas Sertifikasi Halal di Wilayah Glundengan Wuluhan Jember - Istikomah Istikomah; Sofyan Rofi (Mujtama': Jurnal Pengabdian Masyarakat, 2021)
Although the issue ofhalal certification is no longer new, the fact that such certification is now being taken over by the government from the MUI under the act no. 33 year 2014 makes the issue relatively ‘new’ to consider. The legal act might have profound impacts and consequences for the community. This is because there are only few products in the market that have been officially certified halal. Although the community can provide control and supervision of any deviations that may occur on the halal certification, they seem to have low level of awareness of this issue. For this reason, there is a need to socialize halal certification to the community. The present article, therefore, will report on the outcome of community service under the title "strengthening community awareness of Halal certification in the area of Glundengan, Wuluhan".